Behavioral Problems and Psychological Distress Among Seriously Delinquent Youth: Assessing a Mediational Pathway of Parental Monitoring, Peer Delinquency, and Violence Exposure. Issue 2 (March 2021) - Jaggers, Jeremiah W.; Sonsteng-Person, Melanie; Griffiths, Austin; Gabbard, W. Jay; Turner, Marion M.
The onset of behavioral problems in early childhood is associated with an increased frequency of delinquent behavior. A significant amount of youth in the juvenile justice system have histories of mental illness and psychological distress. However, little is known about what factors mediate the relationship between early onset behavioral problems and psychological distress. The present study tested the mediating effect of parental monitoring, antisocial peers, exposure to violence, and gender on the relationship between behavioral problems and psychological distress. A secondary analysis of data from the Pathways to Desistence Study was examined using the serial mediation process proposed by Preacher and Hayes, a significant mediation of the behavior problems–psychological distress relationship was found. The results supported the mediational model in which parental monitoring impacted interaction with antisocial peers which in turn increased the level of violence exposure youth experienced ultimately leading to an increase in psychological distress.